Design and optimisation of passive silicon photonic device for wideband communication system - Xiao, Zhe (2015)
This thesis aims at proposing general and simplified design and optimisation methods for several critical passive photonic components including grating couplers, low loss silicon waveguides and delay lines as well as power splitters etc. In the investigation of grating coupler design, we pioneer the studies on bandwidth mechanism of planar waveguide grating couplers on silicon photonics and derive the bandwidth formula of planar waveguide grating couplers for general cases for the first time. Based on the formula, we further propose the guidelines on how to optimize the bandwidth of grating couplers. As for the coupling efficiency optimisation, we simplify the efficiency optimisation process into several separated steps for individual parameters to reduce the design complexity. We also propose novel design methods for grating couplers to achieve specific functionalities. For waveguide and delay line design, the design procedures using hybrid waveguide schema are discussed for low loss delay line unit with desirable group delay. We design and experimentally demonstrate 50 picoseconds low loss delay line on 300 nm SOI platform. Low propagation loss of ~0.1 dB/cm is achieved on the straight rib waveguide. Taking into account both low loss and desirable delay, a complete design and characterization process for passive delay line is presented. For the studies on splitters, we demonstrate the most compact multimode interference (MMI) splitter up to date, the splitter footprint only takes 1.5×1.8 μm2 area, about one order smaller than the previously reported MMI splitters. Meanwhile, the splitter is polarization insensitive and the measured excess losses for TE and TM modes at telecommunication wavelength are as low as 0.11 dB and 0.18 dB, respectively. As compared to Y-junction splitters which will induce periodic fringes in the spectrum while they are linked with multimode waveguides, the proposed MMI splitter has fringe free spectral response in a wideband range. The design principle and optimisation processes to reduce footprint of MMI splitters while still maintaining low loss performance are discussed. The detailed discussions of design and optimisation methods for individual components and corresponding experimental demonstrations are presented in the separate Chapters.